Eksistensialisme Mulla Sadra - Faiz Faiz (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2013)
This article seeks to analyze Mulla Sadra’s philosophical existentialism. Sadra seeks to provide answers to formulate a concept called the philosophy of wisdom. In outline the teaching philosophy of Sadra include authenticity of the form (asâlat al-wujûd) that the answer to differences in the methods used by the essentialist and existentialist. In this case authenticity of the form (asâlat al-wujûd) spawned several sections related to each other, among other pantheism (wahdat al-wujûd), doubts exist (tashkîk al-wujûd), and movement core (al-harakah al-jawharîyah). Through wahdat al-wujûd (pantheism), Sadra then change the view of the beginning made authenticity essence (asâlat al-mâhîyah) as the core of the reality to an authenticity presence (asâlat al-wujûd). As for tashkîk al-wujûd (doubts exist) is in response to the notion that “form” is God, while the universe is a shadow of it. Sadra gives a different view, he said the absence of the universe (reality) man can not find the “form” the truth, the God who became a grand synthesis of some of the concepts put forward by Islamic thinkers.